Desenvolvimento de uma interface gráfica para análise de testes de vibração em motores - Gonçalves, Ana Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Resonance is not a desirable phenomenon. The objective of performing random vibration tests is to create a vibration spectrum, which simulate a variety of situations which exists in the real-world vibration. These tests are extensively used in the transportation industry, and aim to find possible failures which can affect the equipment analyzed. This work consists in the development of a graphical interface to analyze vibration tests in vehicles’ engines, in order to obtain a complete tool that becomes easy to analyze and understand this type of data, through the visualization of power spectra, resonance, and other mathematical resources, which extend and simplify this type of analysis. Moreover, the developed tool has to be able to convert, to reduce, and to process the data (rough data) provided by automobile manufacturers and companies which perform vibration tests, so it can be used in the developed tool. During the internship period, held in Germany, with the collaboration of the company Robert Bosch GmbH (Automotive Electronics), the first step was an introduction about the subject “Vibration in the automotive industry”. As a result of this work, two graphical interfaces were developed, using the software MATLAB for its development, meeting the requirements for the analysis’ tests. At the end of this work, these interfaces will be available for use and collaboration (resources implementation), by employees from the company Robert Bosch.

O fenômeno da ressonância não é desejável. Testes de vibração buscam criar um espectro para simular as mais variadas situações presentes no cotidiano. Esses testes são exaustivamente utilizados na indústria de transportes, e têm por objetivo encontrar possíveis falhas que podem comprometer os equipamentos analisados. Este trabalho consiste no desenvolvimento de uma interface gráfica para análise de testes de vibração em motores de automóveis, visando obter uma ferramenta completa e que facilite a análise e compreensão desse tipo de dado, por meio da visualização dos espectros de potência, ressonância, além de outros recursos matemáticos que ampliam e facilitam esse tipo de análise. Além disso, a ferramenta desenvolvida deve ser capaz de converter, reduzir e processar, os dados (ainda não processados) fornecidos por fabricantes de automóveis e empresas que realizam testes de vibração, de forma que possam ser utilizados adequadamente na ferramenta de análise desenvolvida. Como resultado desse trabalho, foram desenvolvidas duas interfaces gráficas, utilizando o software MATLAB para seu desenvolvimento, atendendo aos requisitos dos testes, sendo que uma delas contempla a preparação dos dados para posterior análise.
Development of a graphical interface to analize vibration tests data in engines
Keywords: Vibration; Automotive Engines; Data analysis; Vibração; Motores Automotivos; Análise de dados; Vibração – Medição; Automóveis – Motores; Interfaces (Computador); Programas de computador